Evaluation of Nurses’ knowledge about complications of craniotomy - Ammash, Eman Sabah; Ahmed, Sabah Abbas (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): The aim of this study to evaluate nurses' knowledge regarding complications of craniotomy surgery and to determine the relationship between nurses' knowledge and their socio-demographic characteristics.Methods: A descriptive study was designed on a purposive sample (non-probability sample) of 40 nurses in the Neurological Hospital in the intensive care units in Baghdad Governorate, and for the period from 1/12/2022to 28/2/2023, the questionnaire was constructed to collect data and conducted the study, and then determine the validity content of   the questionnaire through a experts panel in adult nursing while internal consistency of reliability through the pilot study. The data was collected through a questionnaire and the data was analyzed through the application of descriptive and inferential statistical methods.Results: The results of   the present study showed that nurses who provide health care to patients with craniotomy in intensive care units have a poor level of knowledge reveals there is no relationship Socio-Demographic Characteristics and the Knowledge of   the Complications of Craniotomy, except the age and educational level that have a relationship at a p value = 0.015 an effective on level of knowledge.Conclusions: The study concluded that nurses in neurosurgery intensive care units in Baghdad Hospital need to be more informed of   the complications of craniotomy surgery.Recommendations: The study recommends conducting an educational program, which is essential to improve nurses' knowledge of   the complications of craniotomy surgery.